2013
DOI: 10.1242/jcs.118174
|View full text |Cite
|
Sign up to set email alerts
|

BAL1/ARTD9 represses the anti-proliferative and pro-apoptotic IFNγ-STAT1-IRF1-53 axes in diffuse large B-cell lymphoma

Abstract: SummaryThe B-aggressive lymphoma-1 protein and ADP-ribosyltransferase BAL1/ARTD9 has been recently identified as a risk-related gene product in aggressive diffuse large B-cell lymphoma (DLBCL). BAL1 is constitutively expressed in a subset of high-risk DLBCLs with an active host inflammatory response and has been suggested to be associated with interferon-related gene expression. Here we identify BAL1 as a novel oncogenic survival factor in DLBCL and show that constitutive overexpression of BAL1 in DLBCL tightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(109 citation statements)
references
References 58 publications
6
100
1
Order By: Relevance
“…Whereas BAL1 has been shown to be overexpressed in diffuse large B cell lymphomas, 41 none of our patients sampled for CD19+ B cells had a previous lymphoma. Disease annotation analysis of the top DMCs in whole blood also pointed to an extensive enrichment of genes associated with lymphoproliferative disorders, including B cell non-Hodgkin's lymphoma.…”
Section: In Pss Cd4+ T Cells and Subsequently Bymentioning
confidence: 64%
“…Whereas BAL1 has been shown to be overexpressed in diffuse large B cell lymphomas, 41 none of our patients sampled for CD19+ B cells had a previous lymphoma. Disease annotation analysis of the top DMCs in whole blood also pointed to an extensive enrichment of genes associated with lymphoproliferative disorders, including B cell non-Hodgkin's lymphoma.…”
Section: In Pss Cd4+ T Cells and Subsequently Bymentioning
confidence: 64%
“…Several studies have shown that STAT3 and STAT5 are required for cell growth, proliferation, survival, invasion and metastasis of many PCa subtypes [1,2,5-10]. In addition, STAT1 has been recently identified as a proto-oncogene product in a variety of cancers, including metastatic PCa (mPCa) [11-23]. A recent study has shown that 29% of clinical human mPCa’s analyzed, constitutively expressed STAT1 and IFN-stimulated genes in vivo [12].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that the ADP-ribosyltransferase-9 (ARTD9), also known as B-aggressive lymphoma protein (BAL1) and PARP9, acts as a novel oncogenic survival factor in high-risk, chemo-resistant, host response (HR) sub-types of diffuse large B-Cell lymphoma (HR-DLBCL) and as a crucial negative and positive co-regulator of IFNγ/STAT1-signaling [23]. ARTD9 is an inactive mono-ADP-ribosyltransferase belonging to the intracellular Diphteria toxin-like glutamate/aspartate-specific mono- and polymerizing-ADP-ribosyltransferase (ARTD) family (also known as PARPs) [38] that also includes the active mono-ADP-ribosyltransferase ARTD8 (also known as PARP14) [38-41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these constitutively expressed ISGs have been characterized as antiviral genes (11). Recently, enhanced levels of constitutively expressed ISGs have been reported in advanced cancers and were often associated with a poor prognosis related to aggressive tumor growth, metastatic spread, resistance to IR/chemotherapy, or combinations of these factors (11)(12)(13)(14)(15)(16)(17)(18). The studies presented in this report are based on the hypothesis that a specific set of constitutively expressed ISGs, whose enhanced expression is by cytotoxic stress, confers a selective advantage to individual tumor clones (5,9,10,13,19).…”
mentioning
confidence: 99%